Algor mortis pattern in dogs, a guide to estimation of time of death - Okene, Ibrahim Abdul-Azeez (Universiti Putra Malaysia Press, 2010)
Although differing methods of estimation of time of death in human forensics have been well documented, there exists paucity of information in the veterinary field. With little accuracy, veterinary pathologists rely on gross post-mortem changes which include autolysis, rigor mortis, livor mortis, and putrefaction in estimating time of death in animals. This study assessed the pattern of temperature drop in six mongrel dogs using commonly available thermometer. Rectal and hepatic temperatures were taken for eight to eleven hours after death at an average ambient temperature of 29 °C (24 °C to 34 °C). Both organs revealed strong regression models which were harnessed to provide a mathematical guide to estimating time of death in the early hours (six to seven hours). Linear model of temperature drop pattern change was considered less cumbersome for field use. The rates of drop were extremely irregular during the study period. This work substantiates the use of algor mortis as an adjunct in estimating time of death in dogs.